Concepción del impacto social en las tesis doctorales de las ciencias biomédicas. - Vega Veranes, Frey (MEDISAN)
Introduction: The conception of the social impact in the doctoral theses in biomedical sciences has required an integrative approach that favors a science orientation and technological innovation in health, for the transfer of biomedical progress and innovations. Objective: To describe the conception of social impact in biomedical sciences dissertations. Methods: An observational, descriptive and cross-sectional study was carried out, from December 2022 to March 2023, of 40 doctoral theses reports —selected by simple random sampling— published in the Repository of Biomedical and Health Sciences Theses in Cuba. For this purpose, the variable conception of social impact in these theses was evaluated according to 3 indicators measured in high, medium and low categories. Results: In the doctoral theses analyzed, 22.5% corresponded to medical sciences; 5.0% to nursing; 22.5% to stomatology and 25.0% either to medical education sciences or to health sciences, respectively. A predominance of reports from dental sciences in the low category was obtained in the 2 indicators related to the contribution and relevance of the social problem they addressed (with 55.5% in each one). Conclusions: It was verified that the conception of social impact in biomedical sciences dissertations was limited, since the most important thing in these ones was to support the scientific impact.